Injury and illness surveillance during the 43rd ISAF youth sailing world championship 2013 in Limassol, Cyprus - Leong, D.; Vaz Pardal, C.; Tan, B.; Lin, C. (British Journal of Sports Medicine, 2014)
Background: Prior studies have indicated that the competitive youth sailor is at risk for sailing-related injuries. Data collected during a large-scale elite youth sailing event is the first step toward developing effective injury/illness prevention strategies in this population. Objective: To describe the incidence, pattern, and severity of sailing-related injuries and illnesses among competitive youth sailors during the 43rd ISAF Youth Sailing World Championship. Design: Prospective descriptive study using the International Olympic Committee injury surveillance system reporting forms. Team officials and medical centre doctors submitted daily surveillance reports.Setting 43rd ISAF Youth Sailing World Championship, 13 to 20 July 2013, Limassol, Cyprus. Participants: All participating sailors in the ISAF World Youth Sailing Championship. Risk factor assessment: The following risk factors were studied: training load, participation in other sports, use of sunscreen/lifejacket, alcohol and drug consumption. Main Outcome Measurements: The occurrence or non-occurrence of sailing-related injuries and illnesses; the number of injuries; the site, type, cause/mechanism of injury; and contributing factors to injuries. Results: 11 (3%) sailors out of 351 sailors reported 11 injuries. The rate of injury was 3.9 injuries per 1000 athlete-days. The most commonly injured site was the foot/toe (36%). The top three types were laceration/abrasion (27%), toe nail injury (27%), and contusion/haematoma/bruise (18%). Most injuries were the result of contact with a stagnant object or an acute event. Treatment was sought in 55%, and 1 sailor withdrew from the competition as a result. Of the 4 illnesses, vomiting/diarrhea was the most common symptom (40%) and the gastrointestional system was most commonly affected (75%). Conclusions: During a high-level sailing competition, 3% of youth sailors reported injuries and 1% reported illness. The injuries were mainly acute events occurring during racing, while illness was mainly of the gastrointestinal system. This data provides us with the basis for future studies and analysis of injury mechanisms and risk factors in elite sailing.